Pathography and Theography: Pain as a Hermeneutic Locus of the Experience of the Sacred - Mildenberg, Emerson (Revista Terra & Cultura: Cadernos de Ensino e Pesquisa; Vol 41 No 78 (2025): Publicação Contínua, 2025)
This article proposes an interdisciplinary reflection on pathography, the narrative of pain and illness, and theography, the narrative of the experience of the divine, with pain as a privileged hermeneutic locus for the experience of the sacred. Based on the assumption that human suffering is not merely a clinical or psychological symptom, but also a spiritual and existential language, the text investigates how pain can become a space for revelation, listening, and reworking of meaning. The analysis integrates contributions from psychoanalysis, narrative theology, and the phenomenology of religion to demonstrate that, in the journey of pain, the subject can be deconstructed and reconstructed in their relationship with God, themselves, and the world. The article also examines how accounts of suffering, whether biblical, clinical, or autobiographical, function as hermeneutic devices that reveal an embodied theology, marked not by dogmatic abstraction, but by the real drama of existence. Ultimately, it is argued that pain, when narrated, becomes a text where the presence (or absence) of the sacred is experienced, interpreted and, often, reinterpreted.